The Role of Whey Supplementation on Sensation Seeking, Parent-child Relationship, Family Communication, Anger and Sex Desire Among Athletes, Athletes Using Whey and Normal Population - Shadanloo, Behshad; Yousefi, Zahra; Parsakia, Kamdin; Hejazi, Sayed Mohammad; Davari Dolatabadi, Muhammadali (Health Nexus, 2023)
The purpose of this research was to examine the role of Whey protein in inducing changes in sensation-seeking, parent-child relationships, family relationships, anger, and sexual desire among regular male athletes, supplement-consuming athletes, and ordinary men in the city of Isfahan. The study population included regular athletes, supplement consumers, and ordinary men in Isfahan. The research method was causal-comparative. The sample size consisted of 30 individuals per group, with the Whey consuming group selected through convenience sampling, and the other two groups were matched and chosen accordingly. The instruments used included scales for family relationships; attachment to parents; sensation-seeking; anger expression, and sexual desire. The research data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (multivariate analysis of covariance) through SPSS software, version 23. The results indicated that the three groups did not significantly differ in the research variables. Thus, it can be stated that Whey protein does not play a significant role in creating changes in the psychological and family-related variables mentioned in the studied groups.